You are right paeagain.. the OA is (A)
But whats confusing me, upon solving we end up with:
3a-2b = ?
But isn't it same as the S(1) itself:
b = 1.5a
2b = 3a
and if we further see our original equation 3a-2b = ?
it tells us 3a = 2b which is what the statement (1) is. So is it solving the question.
I know how you will explain this as 3a-2b= 0 so its sufficient but that is exactly the same as question stem.
This is a C-Trap question. Search this forum for more details on C-Trap.
The question asks what
is the value of 3a-2b.
Statement 1 says the value of 3a-2b is
You will come across such questions .... like is x=0? and one of the statements will be like x^2 + y^2 = 0 which clearly says x=0. It may sound simple, but many people like me will fail to see the logic and fall for the C-Trap.
"You have to find it. No one else can find it for you." - Bjorn Borg